Language‐related differential item functioning between English and German PROMIS Depression items is negligible. Issue 4 (16th October 2016) - Fischer, H. Felix; Wahl, Inka; Nolte, Sandra; Liegl, Gregor; Brähler, Elmar; Löwe, Bernd; Rose, Matthias
Abstract: To investigate differential item functioning (DIF) of PROMIS Depression items between US and German samples we compared data from the US PROMIS calibration sample ( n = 780), a German general population survey ( n = 2, 500) and a German clinical sample ( n = 621). DIF was assessed in an ordinal logistic regression framework, with 0.02 as criterion for R 2 ‐change and 0.096 for Raju's non‐compensatory DIF. Item parameters were initially fixed to the PROMIS Depression metric; we used plausible values to account for uncertainty in depression estimates. Only four items showed DIF. Accounting for DIF led to negligible effects for the full item bank as well as a post hoc simulated computer‐adaptive test (< 0.1 point on the PROMIS metric [mean = 50, standard deviation =10]), while the effect on the short forms was small (< 1 point). The mean depression severity (43.6) in the German general population sample was considerably lower compared to the US reference value of 50. Overall, we found little evidence for language DIF between US and German samples, which could be addressed by either replacing the DIF items by items not showing DIF or by scoring the short form in German samples with the corrected item parameters reported.